Legal Age for Marriage: SDGs and Maslahah Perspectives in Legal Policy Change in Indonesia - Setyawan, Edy; Huda, Muhammad Chairul; Muamar, Afif; Sukardi, Didi; Pangestu, Muhammad Feby Ridho (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
This research aims to identify the impact of the change in legal policy on the protection of human rights and gender equality. This research analyzes the relationship between the aspects influencing legal changes regarding the legal age of marriage in Indonesia from a gender perspective and the SDGs. This study employed a qualitative approach that is based on library research to identify the impact of changes in legal policy. This study also used a juridical approach to capture an overview of Indonesian family law policies as stipulated in the Law Number 16 of 2019 with maslahah theory and Philipus M. Hadjon’s theory of legal protection as the analytical framework. The research results: First, it was found that the issue of the minimum legal age of marriage is part of the legal discovery area, which resulted in the emergence of Law Number 16 of 2019. Second, the gender movement in Indonesia has played a significant role in changing the paradigm of family law towards a more progressive view and a more protective to women’s rights. The integration of Hadjon’s theory of legal protection strengthens the analysis of the impact of changing legal policies on individual rights and gender equality.